THE IMPACT OF PRODUCT QUALITY AND SERVICE QUALITY ON CUSTOMER SATISFACTION - Dewi Lestari; Santi Octavianti; Agus Suhartono (Asosiasi Dosen Muda Indonesia, 2025)
This study investigates the influence of product quality and service quality on customer satisfaction at Istiqomah Mart. The research adopts a quantitative approach using survey methods, with 96 respondents selected through purposive sampling. Data collection was conducted using a structured questionnaire, and the analysis was performed using multiple regression analysis to determine the relationship between variables. The results indicate that both product quality and service quality have a significant positive impact on customer satisfaction. High-quality products and good service encourage customer trust and loyalty, leading to repeat purchases. However, the study also reveals a declining trend in customer satisfaction over time, as seen in the reduction of transaction frequency and unmet sales targets. This suggests that other factors beyond product and service quality may influence customer satisfaction, which were not examined in this research. Given these findings, the study suggests that future research should incorporate additional variables such as pricing strategy, promotional effectiveness, and store ambiance. Additionally, employing qualitative methods such as in-depth interviews could provide deeper insights into customer perceptions. For businesses, continuously improving product offerings and service standards is essential to maintaining customer satisfaction and strengthening market competitiveness.